Chemical and sensory attributes of meat from chickens fed Roystonea regia nuts - Martínez-Pérez, Medeleidy (2025)
Introduction. Previous studies related to the inclusion of palmiche flour, nuts of the royal palm (Roystonea regia), in the diet of broiler chickens showed improvements in quality indicators related to lipid composition in thighs, legs, breasts, and abdominal fat. Objective. To assess the impact of palmiche flour consumption on the chemical and sensory attributes of broiler chicken meat. Materials and methods. The study was conducted over 35 days at the Institute of Animal Science, Mayabeque, Cuba, between February and March 2023, using forty 8-day-old male broilers. Experimental treatments comprised a control group and three inclusion levels of 5, 10, and 15 % of palmiche flour. Moisture and ash content were analyzed in thighs and breasts. Qualitative analysis of color, smell, flavor, dryness, hardness, and juiciness was performed in the control and 15 % inclusion treatments. Overall quality wasassessed quantitatively. Results. Moisture increased in the treatments with 5 and 10 % inclusion compared to controland 15 % treatments, which showed no significant differences (69.92 and 70.45 vs. 65.70 and 65.71 %, respectively). Flavor intensity and overall quality in thighs and breasts improved by including 15 % of palmiche flour. Conclusions. While the consumption of 15 % of palmiche flour did not affect the chemical attributes of the meat, it improved sensory characteristics, particularly flavor, and overall quality of broiler thighs and breasts meat.